TINJAUAN SISTEMATIS: GREEN BONDS DI ASEAN DAN TANTANGAN YANG DIHADAPI - Stefanus Dimas Ryan Saputro (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2023)
The importance of issuing green bond financing for renewable energy and energy efficiency in ASEAN to meet fast-growing energy demand and reduce global temperature rise. Two-thirds of the green bonds issued in ASEAN have been used to finance sustainable projects such as green buildings. However, this does not mean that this issuance is without challenges, one of which is the limited credit absorption capacity. This paper analyzes research related to the issuance of green bonds and the challenges faced in the ASEAN region. This method consists of systematically reviewing the growth and challenges of green bond issuance through journal reviews. This systematic review shows that it is important to issue and mobilize green bonds in the ASEAN region to accelerate the mobilization of renewable energy and other green projects such as green buildings with various challenges.